Pelatihan Strategi Manajemen SDM Untuk Meningkatkan Produktivitas Bisnis Digital Masyarakat di Lingkungan Perumahan Benda Baru Pamulang - Sri Puspita Sari; Bunga Westu Lestari; Yopie Irawan; Riangga Fathurrahman; Aji Rahmansyah (Lembaga Pengembangan Kinerja Dosen, 2025)
The improvement of digital business productivity in Benda Baru Pamulan Housing, South Tangerang, requires attention to human resource (HR) management. Many economic actors in this area struggle to manage HR effectively, limiting their potential to develop digital businesses. The HR Management Training Program aims to educate the community on efficient HR management, including recruitment, training, motivation, and performance evaluation relevant to digital businesses. The implementation of good HR management strategies is expected to enhance digital business productivity and create new business opportunities. This community service activity also aims to improve the skills of Benda Baru residents in creative marketing strategies for small and medium enterprises (SMEs), which have faced challenges in digital marketing and competition. The program is expected to increase the competitiveness of SMEs in a broader market, contribute to economic growth, and enhance collaboration and entrepreneurship within the community